Pengaruh Pemasaran Emosional Terhadap Keputusan Pembelian Melalui Mediasi Citra Merek pada Produk Nike - Adela, Getha; Tecoalu, Melitina (Manajemen Bisnis Kompetensi, 2017)
In a saturated market where competition between producers is increasingly competitive and consumers have many choices in each category of goods / services required. This situation resulted in the desire of consumers to be more important than the needs. This results in a state of mind, emotion, sympathy being dominant, so many companies are looking for ways to make strong connections with consumers emotionally. Emotional connections of consumers are also motivated by the discovery that emotional connections bring consumer loyalty to a higher level, and ultimately hope to improve corporate finance. This journal discusses the influence of Emotional Marketing on Purchase Decision through Brand Image Mediation on Nike Products. This study is quantitative with a sample of 120 respondents who are buyers and users of Nike products in West Jakarta. Collected data were analyzed using Structural Equation Modeling (SEM) technique with SmartPLS program. The results showed that the emotional marketing applied by Nike had a significant positive effect on the brand image as well as the purchase decision with the mediation of brand image. But the brand image does not significantly affect the purchase decision.Keywords: emotional marketing, brand image, purchase decision